Management tool design for eco-efficiency improvements in manufacturing - a case study - Litos, Lampros; Borzillo, Fiammetta; Patsavellas, John; Cockhead, David; Salonitis, Konstantinos (Elsevier, 2017)
As the worldwide GDP is forecasted to double by 2035, the energy demand globally is expected to increase by 34%. The industrial sector is also expected to account for more than 30% of the primary energy demand by 2040. These projections make manufacturing operations even more complicated when combined with predicted long-term inflation of raw material prices and increasingly stringent environmental regulations. Therefore, it has become increasingly more challenging for practitioners in manufacturing to improve their eco-efficiency or to “do more with less”. Traditional manufacturing management tools based on lean principles such as Value Stream Mapping have not been designed to facilitate eco-efficiency improvements. On the other hand, environmental management tools such as Life-Cycle Analysis focus more on improving environmental impacts rather than financial sustainability. This paper addresses the design gap between these tools and proposes an integrated toolkit for eco-efficiency improvements. The toolkit development process and design principles are described through a case study in the flooring industry. Results from each module are validated and the overall output is used to propose a range of applicable solutions to the manufacturer. Paper presented at: Complex Systems Engineering and Development Proceedings of the 27th CIRP Design Conference Cranfield University, UK 10th – 12th May 2017.
Keywords: tool design; eco-efficiency; value stream mapping; life-cycle analyis